Solving Human Resources Management Of Construction Labors Using Mobile Community Network - . Amalia; . Roslidar (Universitas Syiah Kuala, 2010)
A construction labor works on a project based on adetermined interval time. If the construction project is donethen the labor has to find another one. Based on theinterviews conducted to some construction labors in BandaAceh and Medan, they depend totally on the networking andfriendship among the labors in finding a project. sOn theother hand, the labors can survive only for seven days if he isnot working. The proposed solution is developing a jobsearch system for the construction labors using mobileapplication. This system is built using JavaME, RecordManagement Store (RMS) as the storage media, and ShortMessage Service (SMS) as the data connection. This systemapplies distributed system thus it will not cause the processbecomes slow because the limited memory of the cellularphone. This system provides the construction laborsspecification which is needed by the employer and the list ofconstruction labor specification. Job searching will beprocessed again once the labors done with a project. In thisway, the construction labors will continually contracted witha project. Using this system will solve the problem faced bythe construction labor in finding a project and finally achievetheir economis growth.